LncRNA-driven programmed cell death networks: new therapeutic targets for neurological disorders - Zihong Xiong; Zihong Xiong; Chao Sun; Chao Sun; Shiyong Huang (Frontiers in Molecular Neuroscience)
Neural cell death is a critical pathological mechanism underlying the development and progression of central nervous system (CNS) diseases, where programmed cell death (PCD) pathways serve as critical regulatory hubs. In addition to classical apoptosis and autophagy, emerging PCD modalities including necroptosis, pyroptosis, ferroptosis, and cuproptosis exhibit distinct activation patterns in different neurological diseases. Long non-coding RNAs (lncRNAs) have emerged as pivotal regulators of these PCD processes through multiple molecular strategies by modulating chromatin accessibility, assembling signaling complexes, and regulating post-transcriptional processes. These regulatory interactions vary by cellular location and disease stage, influencing cell fate through membrane receptors, kinase cascades, and nuclear transcriptional programs. In various CNS pathologies, specific lncRNAs display dual regulatory capacities—promoting neuronal death by amplifying cytotoxic signals or conferring neuroprotection by inhibiting these pathways. The dynamic lncRNA-PCD interactions offer therapeutic potential through targeted modulation of lncRNA networks to control neuronal survival. Future investigations should prioritize systematic mapping of context-specific lncRNA regulatory networks governing distinct PCD modalities, concurrently advancing spatial epigenomic editing technologies for precise manipulation of these regulatory circuits. Understanding these molecular interactions better will help identify therapeutic targets and guide CNS drug development.